APPLICATION OF MATHLAB APPLICATIONS IN IMPROVING STUDENT COMPETENCE UMSU MATHEMATICS EDUCATION STUDY PROGRAM NUMERICAL METHOD COURSE 2019-2020 ACADEMIC YEAR - Maryanti, Indra (RADJA PUBLIKA, 2021)
This study aims to describe the role of MATHLAB software in numerical method lectures, improve students' ability to solve numerical problems through learning assisted by MATHLAB software, improve students' abilities in formulating algorithms through learning assisted by MATHLAB software, improve students' abilities in programming through assisted learning MATLAB software; and describing student responses after numerical learning assisted by MATLAB software. This research is a quantitative research. To prove the hypothesis and answer the problems in this study, several statistical tests were carried out as follows:1. Test the description of the data, namely: making a data frequency table, testing the average value, and standard deviation.2. Prerequisite test, namely: normality test with Liliefors table and homogeneity test.3. Hypothesis testing, namely: statistical tests to see how much improvement in student competence is using the MATLAB software application in the numerical method course. The tests used are regression and correlation tests to see the increase in student competence using the MATLAB software application. The research method used is experimental. The population of this research is UMSU 7th semester students in the 2019/2020 academic year as many as 98 students.